REVIEW ARTICLE: UTILIZATION OF VARIOUS OF ADSORBENT FROM ACTIVATED CHARCOAL IN INCREASING THE QUALITY OF COOKING OIL - Hasriani, Hasriani; Sitorus, Saibun; Hiyahara, Irfan Ashari (PROSIDING SEMINAR KIMIA, 2023)
Cooking oil is a type of vegetable oil derived from palm plants that has gone through various refining processes. Generally, cooking oil is used repeatedly at high temperatures until the oil is unfit for consumption This results in a decrease in the quality and nutritional value of fried food. In addition, the accumulation of used cooking oil (used cooking oil) can cause environmental pollution. Improving the quality and nutritional value of cooking oil can be done by using the adsorption method. The adsorption method is a method that is carried out by using a number of adsorbents from activated charcoal in the process of refining used cooking oil. Adsorbents from activated charcoal can be made from basic ingredients of agricultural waste such as activated charcoal from coconut shells, corn cobs, snack fruit and others. The adsorbent of activated charcoal can reduce the levels of fatty acids, water content, peroxide levels and acid numbers. The internal adsorption capacity depends on the different adsorbent types, contact time, amount of adsorbent, surface area and structure of the adsorbent and adsorbate concentration. Keywords: Adsorbent, Activated Charcoal, Adsorption Capacity, Used Cooking Oil